India$1 (Bs new space policy: A leap forward for a future space superpowers - Thota, Sreni and Sharma,Sumit (IIPA Digest)
India has a long and proud history of space exploration. The country$1 (Bs first satellite, Aryabhatta, was launched in 1975, and India has since become a major player in the global space community. In recent years, the Indian government has taken steps to further develop the country$1 (Bs space sector. In 2023, the government formed the Indian Space Policy 2023, which outlines the government$1 (Bs vision for the Indian space sector in the coming years. The 2023 space policy is a significant departure from previous policies. It is more liberal in its approach to private sector participation, and it gives greater emphasis to the use of space technology for social and economic development. The policy is also more ambitious in its goals, and it sets out a vision for India to become a leading spacefaring nation.- Reproduced s
Keywords: Space policy, Space superpower